Hydrodynamics and liquid phase residence time distribution in mesh microreactor - Kulkarni, A. A.; Gorasia, A. K.; Ranade, V. V. (Chemical Engineering Science, 2007)
This paper is focused on the experimental analysis of residence time distribution and phase hold-up in a mesh microreactor. A microreactor, where a finely weaved mesh is sandwiched between two flat plates with specific inlets for gas and liquid, is proposed. The microvolumes formed upon sandwiching the mesh are totally connected and thus it yields a view of several interconnected microvolumes. This system is easy to build and does not need precision micromachining. A high-speed photographic analysis yielded the phase distribution for different mesh types over a wide range of operating gas and liquid flow rates. The RTD was studied by measuring the liquid phase conductivity at the outlet of the reactor. Channeling prevailed for mesh with smaller open area. The ADEM was used for fitting the tracer curves with tailing ends. The RTD and the image analysis for all the mesh types showed hysteresis when the gas flow rate was maintained constant and the liquid flow rate was gradually increased and then decreased. (c) 2007 Elsevier Ltd. All rights reserved.
8th International Conference on Gas-Liquid and Gas-Liquid-Solid Reactor Engineering, Indian Inst Technol Delhi, New Delhi, INDIA, DEC 16-19, 2007
Keywords: hydrodynamics; hysteresis; image analysis; microreactor; residence time distribution

Singlejet fluidized beds: experiments and CFD simulations with glass and polypropylene particles - Utikar, Ranjeet P.; Ranade, Vivek V. (Chemical Engineering Science, 2007)
Understanding hydrodynamics of bubbling fluidized beds is crucial in proper design and scale up of these beds. CFD models have shown promise in gaining this understanding. In order to generate confidence in CFD models, predicted time averaged and dynamical characteristics of the bubbling fluidized beds need to be validated against experimental data. This paper describes such studies with rectangular fluidized beds operated with a central jet. Digital image analysis and analysis of wall pressure fluctuations were used for this characterization. Fluidization of two types of particles, glass and polypropylene (PP) was studied at two different initial bed heights of H/D = 1 and 2 with three central jet velocities 5, 10 and 20 m/s. Time averaged as well as dynamical characteristics were studied. The Eulerian-Eulerian two fluid model based on kinetic theory of granular flows was used to simulate these experiments. The predicted results were compared with the experimental data and previously published correlations. Although, there is agreement with experimental data in some aspects, complete agreement was not found. The presented experimental data and comparison with CFD predictions will provide useful basis for further work on understanding bubbling fluidized beds. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: CFD; fluidized beds; hydrodynamics; image analysis; pressure fluctuations; single jet

Experimental analysis of the lift force on bubbles in a swarm - Kulkarni, Amol A. (Chemical Engineering Science, 2008)
The lift force acting on bubbles in a swarm has been estimated by analyzing the instantaneous velocity-time data obtained using LDA in a cylindrical bubble column. Phase distinction was achieved through the multiresolution analysis of the velocity-time data. Several important issues related to the transverse motion of bubbles subjected to a shear field have been discussed quantitatively. The actually measured bubble sizes, the respective slip velocity values in transverse and axial directions and the local shear rates (gamma) enabled the verification of known formulations for the lift coefficient (C-L) for bubbles. At many locations in the column the radial flux of the gas phase by turbulent dispersion and the radial slip were estimated. The radially inward movement of bubbles from low to high axial velocity (from column wall to center, i.e., C-L < 0) was observed at most of the measurement locations. The local lift coefficient was estimated using the transverse drag force and the values support the results from the material balance approach. The estimated C-L values showed a wide variation over the column cross-section. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Bubble; Bubble column; bubble size; hydrodynamics; LDA; lift force

Identification and characterization of flow structures in chemical process equipment using multiresolution techniques - Deshpande, Sagar S.; Joshi, Jyeshtharaj B.; Kumar, V. Ravi; Kulkarni, B. D. (Chemical Engineering Science, 2008)
Planar information of velocity from 2D particle image velocimetry (PIV) and large eddy simulation (LES) data have been studied using multiresolution wavelet transform (WT) formalisms, i.e., discrete and continuous WT. Identification of dominant energy containing structures with their characterization in terms of fractal spectra have been carried out for industrially important equipment exhibiting turbulent behavior. These include annular centrifugal contactor, jet loop reactor, ultrasound reactor, channel flow, stirred tank and bubble column reactor. The characterization of their dynamics based on denoising the data and studying the local energy along the WT scales show sensitive variation and this helps in identifying the size and shape of structures. A dependency is seen between mixing time and the higher order moments of length scale distribution, viz., skewness and kurtosis and a generalized correlation has been built up for important types of equipment and associated flow parameters. The correlation is not only based on the knowledge of reactor geometry and operating conditions but also on the flow structures via their statistical parameters. Wavelet transform modulus maxima (WTMM) methodology has been used to study the evolution of structures and their interaction in a reduced dimensionality by evaluating the fractal spectra. Classification studies have been carried out using principal component analysis (PCA) of the fractal spectra. The results obtained show clear classes for the six types of equipments and delineate regimes to obtain benchmark patterns of flow hydrodynamics based on PCA co-ordinates. This methodology offers a generalized way for the optimal design and operation of different types of reactors. (c) 2008 Published by Elsevier Ltd .
Keywords: Chemical reactors; hydrodynamics; Length scale distribution; mixing; Model reduction; Turbulence; Wavelet transform

Critical review of membrane bioreactor models - Part 2: Hydrodynamic and integrated models - Naessens, W.; Maere, T.; Ratkovich, N.; Vedantam, S.; Nopens, I. (Bioresource Technology, 2012)
Membrane bioreactor technology exists for a couple of decades, but has not yet overwhelmed the market due to some serious drawbacks of which operational cost due to fouling is the major contributor. Knowledge buildup and optimisation for such complex systems can heavily benefit from mathematical modelling. In this paper, the vast literature on hydrodynamic and integrated MBR modelling is critically reviewed. Hydrodynamic models are used at different scales and focus mainly on fouling and only little on system design/optimisation. Integrated models also focus on fouling although the ones including costs are leaning towards optimisation. Trends are discussed, knowledge gaps identified and interesting routes for further research suggested. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: CFD; Costs; hydrodynamics; Integrated model; Modelling

Engineering reactors for catalytic reactions - Ranade, Vivek V. (Journal of Chemical Sciences, 2014)
Catalytic reactions are ubiquitous in chemical and allied industries. A homogeneous or heterogeneous catalyst which provides an alternative route of reaction with lower activation energy and better control on selectivity can make substantial impact on process viability and economics. Extensive studies have been conducted to establish sound basis for design and engineering of reactors for practising such catalytic reactions and for realizing improvements in reactor performance. In this article, application of recent (and not so recent) developments in engineering reactors for catalytic reactions is discussed. Some examples where performance enhancement was realized by catalyst design, appropriate choice of reactor, better injection and dispersion strategies and recent advances in process intensification/ multifunctional reactors are discussed to illustrate the approach.
21st National Symposium on Catalysis (CATSYMP), CSIR Indian Inst Chem Technol, Hyderabad, INDIA, FEB 11-13, 2013
Keywords: Catalyst; effectiveness; engineering; hydrodynamics; reactors

Two-phase flow in metal monoliths: hydrodynamics and liquid-liquid extraction - Deshpande, Jaydeep B.; Gosavi, Abha; Kulkarni, Amol A. (Canadian Journal of Chemical Engineering, 2014)
This work aims to explore the application of metal monoliths as a scale-up option for efficient liquid-liquid extraction. The pressure drop, mass transfer and residence time distribution are measured for low Ca (approximate to 10(-5)) with monoliths having three different cell densities. The cross-over section between two monoliths was seen to enhance mixing in the column. However, the RTD of two-phase liquid-liquid up-flow was inferior to the single phase RTD. For higher cell density substrates, the cross-over zones seem to cause trapping of slugs due to non-superimposing channel ends. Relatively high shear rates through the film of continuous phase helped enhance the mass transfer rates, thereby helping to achieve the desired extraction in a short column. The entrance sections and cross-over zones between the monoliths adversely affected the extraction for higher cell density monoliths. The analysis of data supports use of low cell density monolith for better performance and scale up.
Keywords: capillary; hydrodynamics; liquid-liquid extraction; monolith; slug flow